ANALISIS IDENTITAS VISUAL PADA IKLAN FASHION BRAND INTERNASIONAL DKNY - SANDY RISMANTOJO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Brand Identity and brand image are important parts of the branding process that must be managed in a sustainable way in order to seek and gain attention from their target audience. Life and death of a fashion brand depends on how the brand manages its image, products and how the brand establishes an intense relationship with its target audience. DKNY is an internationally renowned fashion brand that can be said to have succeeded in managing its brand identity and brand image by developing visual characteristic that no other fashion brand has. This essay will deeply analyze the DKNY’s visual characteristic by reading the icons and index of DKNY fashion advertisings. Keywords: advertising; branding; fashion; icon; index